Rivalitas Hidropolitik: Meninjau Kerjasama di Balik Konflik Sungai Brahmaputra Antara India dan China - Digna Defianti; Arla Rahma Tsabita; Dandy Setiawan Nur Alif; Muhammad Al Hanif Candraputra; Shafira Zezy Aradifa; Valli Sinatra Yusuf; Yulianus Bramandito Ernanta S. (Department of International Relations, Brawijaya University, 2024)
Competition for water resources is one of the most important problems in the world given the limited availability of clean water sources. Several countries in the world depend on their water supply needs to other countries because they are unable to meet their own clean water needs. Therefore, cooperation in the field of waters is carried out by a number of countries to be able to overcome conflicts that occur due to water problems. As is the case with the conflict between China, Bangladesh and India regarding the Brahmaputra River, the river that crosses these three countries is at the same time very important for the supply of clean water for these three countries. So the formulation of the problem in this paper is